Accents, Not Just Prosodic Boundaries, Influence Syntactic Attachment. (June 2018) - Carlson, Katy; Tyler, Joseph C.
Traditionally, pitch accents are understood to relate to the information structure of a sentence and its discourse connections, while prosodic boundaries indicate groupings of words and affect how constituents attach into a syntactic structure. Here, we show that accents also affect syntactic attachment in multiple different syntactic structures. Three auditory questionnaires on ambiguous attachment sentences (such as Tom reported that Bill was bribed [last May] ) find that accenting the higher or lower verb ( reported or bribed ) increases the attachment of the final adverbial phrase as a modifier of the accented verb. A fourth experiment shows that accents on verbs or object nouns (in sentences like Jenny sketched a child [with crayons] ) also increase the attachment of the final prepositional phrase to the accented head (sketched with crayons versus a child with crayons). Accent effects were small but consistent across sentences with different levels of bias and did not depend on prosodic boundaries. The results suggest that focused elements are important to the main assertion of the sentence and therefore draw the attachment of upcoming material (though the salience of attachment sites may also be important). The results also demonstrate that both prosodic phrasing and pitch accents can affect basic syntactic structure.